Polityczne znaczenie ruchu ślązakowskiego w obliczu plebiscytu na Śląsku Cieszyńskim = The political importance of the szlonzakian movement in the Cieszyn Silesia plebiscite - Wnętrzak, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article deals with the political importance of the Szlonzakian movement in Cieszyn Silesia in a crucial time for this area, after the fall of the Austro-Hungarian monarchy and announcement of a plebiscite which aimed at establishing its dependency from Poland or Czechoslovakia. The announcement of the plebiscite in September 1919 was perceived in Poland as the first step to a definite win in the battle for Silesia.
Keywords: Ruch ślązakowski; Śląsk Cieszyński; Polska - historia - 1918-1939